1994
DOI: 10.1161/01.atv.14.3.386
|View full text |Cite
|
Sign up to set email alerts
|

Relation of aortic stiffness to factors modifying the risk of atherosclerosis in healthy people.

Abstract: To identify factors predicting aortic stiffness, we studied the modulus of elasticity of the thoracic aorta in relation to sex, obesity, blood pressure, physical activity, smoking, ethanol consumption, salt intake, and serum lipid and insulin levels in 55 healthy people born in 1954. A transverse cine magnetic resonance image of the thoracic aorta was made, and the modulus of elasticity was determined as brachial artery cuff pulse pressure/aortic strain, where strain was determined as the ratio of pulsatile ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
47
1
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 36 publications
6
47
1
3
Order By: Relevance
“…Generally, a positive association has been found between insulin levels and arterial stiffness, but in many of these studies no adequate adjustments for HR were made. [28][29][30][31][32][33] However, in the three recently published studies, using the same methods as in the present study to measure PWV, no independent relationship between insulin and PWV could be identified after adjustment was made for SBP or mean BP, HR, sex, and age, 10-12 so at first glance our findings are not consistent with these results. Another finding that at first glance appears to be in contrast with the findings in the present study comes from Yki-Jarvinen and coworkers, who in different groups of subjects have shown that infusion of insulin producing acute hyperinsulinaemia leads to a marked decrease in large arterial stiffness.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Generally, a positive association has been found between insulin levels and arterial stiffness, but in many of these studies no adequate adjustments for HR were made. [28][29][30][31][32][33] However, in the three recently published studies, using the same methods as in the present study to measure PWV, no independent relationship between insulin and PWV could be identified after adjustment was made for SBP or mean BP, HR, sex, and age, 10-12 so at first glance our findings are not consistent with these results. Another finding that at first glance appears to be in contrast with the findings in the present study comes from Yki-Jarvinen and coworkers, who in different groups of subjects have shown that infusion of insulin producing acute hyperinsulinaemia leads to a marked decrease in large arterial stiffness.…”
Section: Discussioncontrasting
confidence: 85%
“…1 Several other studies have examined the relationship between insulin and arterial stiffness. [15][16][17][18][28][29][30][31][32][33] Many different methods and indices have been used Table 4 because P>0.05: log of VLDL cholesterol, LDL cholesterol, HDL cholesterol, log of triglycerides, log of glucose, history of diabetes, diastolic BP, treatment of hypertension, BMI, waist/hip ratio, microalbuminuria, left ventricular mass index, smoking, alcohol consumption; X vs o5 beverages per day, physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some previous studies have shown an inverse association between insulin levels and arterial elasticity. 5,9,31 The mechanisms by which insulin level may effect arterial distensibility are not well elucidated but may include the effects of insulin, promoting vascular wall smooth muscle hypertrophy 37 and collagen tissue synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reports concerning serum lipoproteins in the context of arterial stiffness have been controversial. Some investigations have reported positive associations between serum cholesterol concentration and aortic distensibility 6,8,9 ; some, negative associations 10,11 ; and others, no association. 12,13 In the current study, we investigated the elastic properties of large arteries in the ascending and descending parts of the thoracic aorta by using magnetic resonance imaging (MRI) and in the extracranial common carotid artery by using high-resolution ultrasound.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Convential cardiovascular risk factors (eg, high low-density lipoprotein (LDL)-cholesterol), in turn, have been associated with increased carotid IMT, decreased brachial FMD and decreased arterial elasticity. 1,[7][8][9][10][11][12][13] Circulation Journal Vol.72, January 2008 Genetic factors play a role in the pathogenesis of atherosclerosis, partly by influencing plasma lipoprotein concentrations. 4,[14][15][16][17][18] Heritability estimates of interindividual differences in IMT range from 30% to 40% but the specific genes contributing to this variability are unknown.…”
mentioning
confidence: 99%